Audiovisual media effectiveness in post-cataract surgery care education in National Eye Center Cicendo Hospital - Syabariyah, Sitti; Muhtar Hidayat, Tantan; Sofiyah, Yusi; Khairatun Hisan, Urfa (Intelektual Pustaka Media Utama, 2023)
Currently, eye surgery is the only viable solution to reserve blindness in cataract patients. Nonetheless, post-cataract surgery care plays an important role in the effectiveness of cataract surgery. To ensure the success of post-cataract surgery, healthcare providers must support patients with adequate knowledge regarding post-cataract surgery care. In this study, we investigate the effectiveness of audiovisual media in post-cataract surgery care education on improving patients’ knowledge. This quasi-experimental study is designed with one group pre-test and post-test approach. We recruited a total of 58 participants aged ≥40 years with senile cataract diagnosis who underwent cataract surgery by phacoemulsification in one eye using local anesthesia or neurolept, with visual acuity in the unoperated eye ≥0.08, and without hearing loss. Participants were given complementary post-surgery education through audiovisual media for 7 minutes and participants were instructed to fill out the questionnaire about post-cataract surgery care prior to and after getting the complementary audiovisual media education. The collected data were analyzed using the frequency distribution analysis and Wilcoxon test. The findings suggest that the application of audiovisual media in post-cataract surgery care education significantly increases patients’ knowledge (p-value<0.001). This study concludes that providing education through audiovisual media is recommended for post-cataract surgery patients.